Bratfest at Tiffany's : a clique novel - Harrison, Lisi. (New York : Little, Brown, 2008)
When male students from Briarwood join the all-girl Octavian Country Day at the beginning of eighth grade, Massie makes a rule that none of the girls on the Pretty Committee can have anything to do with them, trying to protect the girls' social status.
"Poppy."
Keywords: Middle schools -- Fiction; Schools -- Fiction; Cliques (Sociology) -- Fiction; Interpersonal relations -- Fiction; Westchester County (N.Y.) -- Fiction